2009
DOI: 10.1097/aap.0b013e3181933f09
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Improves the Success Rate of a Sural Nerve Block at the Ankle

Abstract: : Ultrasound guidance using the lesser saphenous vein as a reference point results in a more complete and longer lasting sural nerve block than does a traditional approach using surface landmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 17 publications
0
35
0
10
Order By: Relevance
“…Based on the intimate relationship between the lesser saphenous vein and the SN, Cartwright et al 10 reported on the cross-sectional area of the SN in the distal calf. Redborg et al 7 reported that ultrasound guidance improved the quality of SN block in comparison to a traditional landmark-based technique. Kamm et al 6 evaluated the usefulness of ultrasound to improve positioning of the recording needle for nerve conduction studies of the SN.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the intimate relationship between the lesser saphenous vein and the SN, Cartwright et al 10 reported on the cross-sectional area of the SN in the distal calf. Redborg et al 7 reported that ultrasound guidance improved the quality of SN block in comparison to a traditional landmark-based technique. Kamm et al 6 evaluated the usefulness of ultrasound to improve positioning of the recording needle for nerve conduction studies of the SN.…”
Section: Discussionmentioning
confidence: 98%
“…Based on extrapolating the results from our sural nerve study, 10 we hypothesized a success rate of 95% in group US and 50% in group LM. With a power of 0.8 and a type I error rate of 0.05, 18 subjects were required for the paired comparison in which each subject served as his/her own control.…”
Section: Discussionmentioning
confidence: 99%
“…In this RCT, we were imaging the sural nerve at the distal fibula. 6 The image provided for the sural nerve reveals a circular hyperechoic structure immediately beneath the lesser saphenous vein (Fig. 4).…”
mentioning
confidence: 99%